Eliciting family concerns and priorities through the Routines-based Interview. Issue 2 (3rd April 2019) - Hughes-Scholes, Carolyn H.; Gavidia-Payne, Susana; Davis, Kate; Mahar, Nicole
ABSTRACT: Background: Research has demonstrated that having an understanding of families' everyday routines is important when planning interventions, yet the nature of the information revealed by families about their daily lives has been scarcely documented. The aim of this study was to examine the concerns and priorities of families with a child with a developmental disability elicited through the Routines-based Interview (RBI). Method: RBIs were conducted by early childhood intervention (ECI) professionals with 16 families with a child aged between 4 months and 5 years. Interviews were audiotaped and transcribed verbatim and analysed using thematic analysis. Results: Findings revealed that families were concerned about their child's development and behaviour; made accommodations to everyday routines for their child; and reported priorities for the intervention. Conclusion: Tools, such as the RBI, are important to generate information that can assist ECI professionals to design interventions that are family-centred, contextualised, and embedded in everyday family life.